Legal Status of The Li'an Children Recognition: Comparison of The Mazhab Malikiyah and The Compilation of Islamic Law - Bahri, Andi Syamsul (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
This study discusses the Legal Status of Li'an Child Recognition: Comparison of the Madzhab Malikiyah and the Compilation of Islamic Law. The essence of the problem in this study lies in the difference of opinion on the time limit for the recognition of li'an children or submission to court according to the Madzhab Malikiyah and KHI. The purpose of the study was to compare the Madzhab Malikiyah of Law and the Compilation of Islamic Law about Li'an children. With this research, it is hoped that it can become a reference for science in general and Islamic science, especially for legal science. The researcher uses library research with a normative approach. Data collection is done by collecting and reviewing books, journals and e-books related to marriage, the four madzhab of jurisprudence, compilation of Islamic law and Li'an. This study results that the Mazhab Maliki provides for the wife's holy period of three menstruation, or one menstruation is the time limit for denying a child for the husband, while according to the Compilation of Islamic Law it cannot show the time limit for the husband to deny the child. The Compilation of Islamic Law only emphasizes when submitting the denial of a child to the religious court that a husband who wishes to file a denial of a child must not exceed 6 months from the time the child is born. As for the comparison of the Li'an oath, Imam Maliki and the Compilation of Islamic Law have elements of the same opinion and refer to Islamic Law, namely: Li'an is carried out before a judge, Li'an results in divorce between husband and wife after Li'an completed, which causes a permanent divorce, and it is forbidden for both parties to get back together. Meanwhile, in terms of differences only lies in the time limit for the denial of Li'an's children